Risk of new tumor, carotid stenosis, and stroke after stereotactic radiosurgery for pituitary tumor: A multicenter study of 2254 patients with imaging follow-up - Dumot, Chloe; Mantziaris, Georgios; Dayawansa, Sam; Brantley, Carson; Lee, Cheng-Chia; Yang, Huai-Che; Peker, Selcuk; Samanci, Yavuz; Mathieu, David; Tourigny, Jean-Nicolas; Martinez Moreno, Nuria; Martinez Alvarez, Roberto; et al. (Neuro-oncology, 2024)
BACKGROUND: A higher risk of secondary brain tumor, carotid stenosis, and stroke has been reported after conventional sella irradiation for pituitary neuroendocrine tumors (PitNET). Stereotactic radiosurgery (SRS), which is a more focused approach, is now increasingly used instead. The aim was to assess the risk of secondary brain tumor, carotid stenosis/occlusion, and stroke after SRS. METHODS: In this multicentric retrospective study, 2254 patients with PitNET were studied, 1377 in the exposed group, and 877 in the control group. RESULTS: There were 9840.1 patient-years at risk for the SRS and 5266.5 for the control group. The 15-year cumulative probability of secondary intracranial tumor was 2.3% (95% CI: 0.5%, 4.1%) for SRS and 3.7% (95% CI: 0%, 8.7%) for the control group (P = .6), with an incidence rate of 1.32 per 1000 and 0.95 per 1000, respectively. SRS was not associated with an increased risk of tumorigenesis when stratified by age (HR: 1.59 [95% CI: 0.57, 4.47], Pp = .38). The 15-year probability of new carotid stenosis/occlusion was 0.9% (95% CI: 0.2, 1.6) in the SRS and 2% (95% CI: 0, 4.4) in the control group (P = .8). The 15-year probability of stroke was 2.6% (95% CI: 0.6%, 4.6%) in the SRS and 11.1% (95% CI: 6%, 15.9%) in the control group (P < .001). In Cox multivariate analysis stratified by age, SRS (HR 1.85 [95% CI:0.64, 5.35], P = .26) was not associated with risk of new stroke. CONCLUSIONS: No increased risk of long-term secondary brain tumor, new stenosis or occlusion, and stroke was demonstrated in the SRS group compared to the control in this study with imaging surveillance.
Keywords: nádory hypofýzy; nádory mozku; Humans; lidé středního věku; Brain Neoplasms; dítě; Stroke; Child; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Neoplasms, Second Primary; senioři; lidé; radiochirurgie; cévní mozková příhoda; Adult; sekundární malignity; Radiosurgery; Pituitary Neoplasms; Follow-Up Studies; ženské pohlaví; Carotid Stenosis; Male; Middle Aged; Retrospective Studies; Adolescent; prognóza; Aged, 80 and over; stenóza arteria carotis; Young Adult; senioři nad 80 let; retrospektivní studie; mužské pohlaví; Prognosis; následné studie; mladiství; Risk Factors